Cannabinoid-induced actomyosin contractility shapes neuronal morphology and growth - Roland, Alexandre B; Ricobaraza, Ana; Carrel, Damien; Jordan, Benjamin M; Rico, Felix; Simon, Anne; Humbert-Claude, Marie; Ferrier, Jeremy; McFadden, Maureen H; Scheuring, Simon; Lenkei, Zsolt (eLife, 2014)
Endocannabinoids are recently recognized regulators of brain development, but molecular effectors downstream of type-1 cannabinoid receptor (CB1R)-activation remain incompletely understood. We report atypical coupling of neuronal CB1Rs, after activation by endo- or exocannabinoids such as the marijuana component ∆9-tetrahydrocannabinol, to heterotrimeric G12/G13 proteins that triggers rapid and reversible non-muscle myosin II (NM II) dependent contraction of the actomyosin cytoskeleton, through a Rho-GTPase and Rho-associated kinase (ROCK). This induces rapid neuronal remodeling, such as retraction of neurites and axonal growth cones, elevated neuronal rigidity, and reshaping of somatodendritic morphology. Chronic pharmacological inhibition of NM II prevents cannabinoid-induced reduction of dendritic development in vitro and leads, similarly to blockade of endocannabinoid action, to excessive growth of corticofugal axons into the sub-ventricular zone in vivo. Our results suggest that CB1R can rapidly transform the neuronal cytoskeleton through actomyosin contractility, resulting in cellular remodeling events ultimately able to affect the brain architecture and wiring.
Keywords: cytoskeleton; myosin; dendrite; axon; cannabis; RhoA